Short Communication: Antimycotic activity and phytochemical screening of fungal endophytes associated with Santalum album - ASHWANI TAPWAL; SWETA PRADHAN; SURESH CHANDRA; RASHMI RASHMI (Nusantara Bioscience, 2016)
Abstract. Tapwal A, Pradhan S, Chandra S, Rashmi. 2016. Antimycotic activity and phytochemical screening of fungal endophytes associated with Santalum album. Nusantara Bioscience 8: 14-17. The heartwood of Santalum album constitutes the central part of the tree is valued for its fragrance. The wood and oil are utilized in medicine. Sandalwood oil is extensively used in perfumery, cosmetics, aromatherapy, and pharmaceutical industry. The endophytic microorganisms inhabiting the plant tissues are expected to mimic some of the metabolites of its host. This study was aimed to isolate and screen the fungal endophytes inhabiting the Santalum album for antimicrobial activity and for the presence of important phytochemicals. Five fungal endophytes isolated from different parts of S. album have exhibited antimicrobial potential against Fusarium oxysporum in the range of 5.0-40.4%. The isolated endophytic fungi also indicated the presence of alkaloids, phenolics, and tannins, flavonoids, carbohydrates and glycosides, terpenoids, amino acids and proteins.